Nonlinear Finite Element Analysis of the Fluted Corrugated Sheet in the Corrugated Cardboard - Zhiguo Zhang; Tao Qiu; Riheng Song; Yaoyu Sun (Advances in Materials Science and Engineering)
The choice of corrugated medium, flute size, combining adhesive, and linerboards can be varied to design a corrugated board with specific properties. In this paper, the nonlinear finite element analysis of the fluted corrugated sheet in the corrugated cardboard based on software SolidWorks2008 was investigated. The model of corrugated board with three or more flutes is reliable for stress and displacement measurement to eliminate the influence of the number of flutes in models. According to the static pressure test, with the increase of flute height H or arc radius of flute, the maximum stress in the models decreased and the maximum displacement increased. However the maximum stress and maximum displacement in the models increase nonlinearly in the static pressure test with the increase of the flute angle θ. According to the drop test, with the increase of flute height H, the maximum stress of goods on the upper board in the drop test decreased. The maximum stress of the model in the drop test decreases firstly and then increases with the increase of flute angle, and the optimal flute angle θ could be 60° for corrugated board. All the conclusions are consistent with experimental data or product standards.